The Water-energy Nexus in the Island of Crete, Greece - Vourdoubas, John (Environmental Management and Sustainable Development, 2021)
Water and energy are valuable resources in our contemporary societies. Their demand worldwide is increasing while they are interconnected and interlinked. Aim of the current work is to investigate the nexus between water and energy in the island of Crete, Greece. The use of water in electricity generation and in fuels production is investigated as well as the electricity utilization in water pumping, transportation, processing and distribution. Our results indicated that the annual electricity consumption in Crete is at 4,793 KWh/capita while the annual water consumption is at around 763.9 M3/capita to 962.2 M3/capita. The main fuels used in electricity generation in Crete are fuel oil and diesel oil that are imported. Among renewable energies solar-PV and wind energy are mainly used for power generation. Generation of solar-PV and wind electricity requires limited water resources while in water-cooled thermal power stations brackish and desalinated water is mainly used. Crete has sufficient water resources which though are unevenly distributed along the island. Groundwater is the main water source used while agriculture is the main sector of water consumption. Electricity is necessary in all stages of water utilization in Crete. The results indicated that the nexus between water and energy in Crete is asymmetrical and uneven. Electricity generation is not significantly depended on freshwater resources while water utilization is depended on electricity. These findings could be useful in designing the optimum management policies regarding the long term sustainability of these valuable resources in Crete.